Determination of Service Quality, Facilities, Infrastructure, Competence on Loyalty Mediated by Patient Satisfaction at M.Sani Hospital, Karimun Regency - Andre Resta; Wibisono, Chablullah; Satriawan, Bambang (Universitas Pamulang, 2024)
This study shows that the people of Karimun Regency tend to choose neighboring countries or Batam City to obtain better healthcare services. This is due to several factors, such as a decline in the number of patient visits to RSUD Muhammad Sani from January to March 2024. This quantitative research aims to examine the influence of these factors on patient loyalty. The results indicate that service quality has a significant direct effect on patient loyalty, although it does not significantly impact patient satisfaction. Conversely, infrastructure and competence do not have a significant effect on patient loyalty but do show a significant influence on patient satisfaction. Employee competence does not have a significant direct impact on patient loyalty but significantly affects patient satisfaction. Furthermore, the findings reveal that patient satisfaction cannot mediate the influence of service quality, infrastructure, and competence on patient loyalty. Therefore, to improve patient loyalty, RSUD Muhammad Sani needs to directly enhance service quality, while improvements in infrastructure and employee competence have a greater impact on increasing patient satisfaction, which is ultimately expected to contribute to overall patient loyalty. Future research could be expanded by broadening the scope of the study, increasing the sample size, and including variables that could determine loyalty and satisfaction at RSUD Muhammad Sani in Karimun Regency, thereby establishing a state-of-the-art foundation for subsequent research.